Select Internet Resources on Acoustics - Angela R. Davis (Issues in Science and Technology Librarianship)
The article lists online resources related to acoustics including websites, databases, and journals "Advances in Acoustics and Vibration", "EURASIP Journal on Audio, Speech, and Music Processing", and "Photoacoustics".